Answer:
x= -17/6
Step-by-step explanation:
10=-9/2x-7-3/2x
multiply all by 2
20=-9x-14-3x
add -9x to -3x
20=-12x-14
replace 20 with -12x and put -12x as a positive
12x=-14-20
add -14 to -20
12x=-34
divide both sides by 12
x= -17/6
Answer:√5 - √2
Step-by-step explanation:
= √(5 + 2 - 2√10 )
= √{(√5)² +(√2)² - 2.√5.√2}
= √(√5 - √2)² (by identity a² + b² -2ab = ( a-b)²)
= √5 - √2
5√5 = 11.8033989 or -2√5+7
Answer:
B:Both powers should be in the denominator with positive exponents.
Step-by-step explanation:
We are given that Tyler simplified an expression
We have to find an error which Tyler makes in her simplification
Step 1:
Step 2:
Step 3:
Hence, Tyler's error is both exponents should be denominator with positive exponents.
Answer:B:Both powers should be in the denominator with positive exponents.
Answer:
Step-by-step explanation:
1
Tyler correctly rewrote x^(-3) as ------- , but
x³
1
he incorrectly wrote y^(-9) as ---------
y^(-9)
Both x^9 and y^9 should be in the denominator. This corresponds to the 2nd given possible answer.
Answer:
Step-by-step explanation:
I think it would be something like this, maybe
-10.3+y=5.2
-103/10+y=52/10
(-103)+10y/10=2*2*13/2*5
y=31/2
which is 15.5